2022
DOI: 10.1124/jpet.121.001055
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Anwulignan on Gastric Injury Induced by Indomethacin in Mice

Abstract: Anwulignan (AN) is a monomer lignan from Schisandra sphenanthera Rehd. et Wits (Schisandra sphenanthera fructus, Schisandra sphenanthera). The protective effect of AN against the indomethacin (IND)-induced gastric injury to mice and the related mechanism of action was investigated in this study. The effect of AN was mainly assessed by observing the gastric tissue morphology, gastric ulcer index (GUI), ulcer inhibition rate (UIR), gastric juice volume (GJV) and pH value. Chemical colorimetry, immunofluorescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The activation of oxidative stress and increased levels of apoptosis-related factors exacerbate the extent of DILI (Ezhilarasan, 2023;Pomacu et al, 2023). The results of our previous studies indicated that Anwulignan had relatively good anti-oxidative stress and anti-apoptotic effect in all other tissue injuries (C. Liu et al, 2021;J. Liu et al, 2022;Yuchong et al, 2020), suggesting that Anwulignan can play a role in clinical diseases.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The activation of oxidative stress and increased levels of apoptosis-related factors exacerbate the extent of DILI (Ezhilarasan, 2023;Pomacu et al, 2023). The results of our previous studies indicated that Anwulignan had relatively good anti-oxidative stress and anti-apoptotic effect in all other tissue injuries (C. Liu et al, 2021;J. Liu et al, 2022;Yuchong et al, 2020), suggesting that Anwulignan can play a role in clinical diseases.…”
Section: Discussionmentioning
confidence: 86%
“…The results of our previous studies indicated that Anwulignan had relatively good anti-oxidative stress and anti-apoptotic effect in all other tissue injuries (C. Liu et al, 2021; J. Liu et al, 2022; Yuchong et al, 2020), suggesting that Anwulignan can play a role in clinical diseases.…”
Section: Discussionmentioning
confidence: 93%